Coaching achievements for young volleyball athletes at the sportive discipline club (diasporas) of Kendal regency - Arifin, Wahyu; Amrullah, Aziz (Universitas Suryakancana, 2025)
Performance coaching is one form of training programs that organizations can implement to develop athletes to excel. Proper coaching will create a generation of quality athletes in their fields. The objective of this research is to analyze the performance coaching of volleyball athletes in the Diasporas Club of Kendal Regency. The research method used is quantitative, Data collection techniques include questionnaires, observations, and interviews. Data analysis techniques use descriptive statistics. The research results show that the performance coaching conducted by the Diasporas Club of Kendal Regency is categorized as good. The nurturing process is considered good. The coaches involved are professional coaches. The facilities and infrastructure owned by the Diasporas Club of Kendal Regency are categorized as good. However, in terms of funding, Diasporas Kendal Regency still needs assistance to develop its training programs.